A Moving Boundary Modeling Approach for Heat Exchangers with Binary Mixtures. (September 2017) - Kim, Donghun; Ziviani, Davide; Braun, James E.; Groll, Eckhard A.
Abstract: In this paper, a modeling approach for a heat exchanger that uses a binary mixture is presented. A moving boundary method assuming a linear spatial distribution of enthalpy could result in a considerable steady state prediction error, due to the temperature glide of a binary mixture. Motivated from this, a more accurate moving boundary method that incorporates analytic enthalpy distributions is presented. The enthalpy profiles are derived by defining a specific heat capacity at each thermodynamic phase of a binary mixture and by solving crossflow heat transfer equations. The proposed approach results in accurate predictions compared with those of a detailed model using the Finite Volume Method (FVM). The corresponding computation time is two to three times slower than that of a conventional moving boundary approach, but the approach is still computationally advantageous compared with the FVM model.